Evaluation of microstructural changes in fresh cement paste using AC impedance spectroscopy vs. oscillation rheology and 1H NMR relaxometry. (November 2021) - Huang, Tingjie; Yuan, Qiang; Zuo, Shenghao; Li, Baiyun; Wu, Qihong; Xie, Youjun
Abstract: AC impedance spectroscopy (ACIS) is a promising technique for monitoring the microstructure evolution of fresh cement paste in real-time. This paper compared the change of bulk electric resistivity (ρbulk ) obtained from ACIS with the developments of storage modulus (G′) and the mean transverse relaxation times (T2 ) of fresh Portland cement pastes within 5 h. It was found that the three different phases (Phase I, II, and III) on the microstructural build-up process of fresh paste can be accurately distinguished by analyzing ρbulk, as well as G′ and T2 . The use of ρbulk fails to characterize the microstructural changes in Phase I due to the great sensitivity on the electrical conductivity of the interstitial solution. However, it can successfully reflect the developing features of microstructure in Phases II and III, and reliably evaluate the impacts of water to cement ratio, superplasticizer, and supplementary cementitious materials on the microstructural development.